Study on the efficacy of furosemide nebulization in transient tachypnea of newborn – A case–control study - A. Kaivalya; R. H. Gobbur; S. S. Kalyan Shettar; M. M. Patil (BLDE University Journal of Health Sciences)
OBJECTIVE: This study compares the efficacy of furosemide nebulization versus normal saline nebulization in treating transient tachypnea of the newborn (TTN). METHODS: A prospective case-control study was conducted on 100 neonates diagnosed with TTN, who were randomly assigned to two groups. Group A received furosemide nebulization, while Group B received saline nebulization. The neonates were monitored for oxygen requirement, NICU stay, breastfeeding initiation, weight loss, and other clinical outcomes. RESULTS: Furosemide nebulization resulted in a significantly shorter NICU stay, reduced oxygen requirement, and earlier initiation of breastfeeding compared to saline nebulization. Both groups had a 100% discharge rate, with no adverse effects observed in either group. CONCLUSION: Furosemide nebulization is a safe and effective treatment for TTN, offering superior outcomes in terms of oxygen therapy reduction, faster recovery, and shorter NICU stays compared to normal saline nebulization.